Evaluation of KCl-EDTA-, CaCl2- DTPA-, CaCl2-DTPA-TEA extractants for estimating available Cu in soils - Balláné Kovács, Andrea; Kincses, Sándorné; Nagy, Péter Tamás (Acta Agraria Debreceniensis, 2007)
KCl-EDTA-, CaCl2-DTPA-, CaCl2-DTPA-TEA extraction methods were compared to determine the plant available Cu amounts in the soil samples. In the soil extracts, the amounts of copper were measurable. In the buffered CaCl2-DTPA-TEA extracts, data showed the lowest values. On the applied soils, a correlation was observed between plant removal and soil Cu using extractants mentioned above. The closest correlation appeared in the case of sandy soils. From the results of statistical analysis, it appears that soil properties may play role in the efficiency of the extraction using either CaCl2-DTPA or KCl-EDTA solutions. To establish more reliable relations, further studies with different types of soils are needed.